PENGEMBANGAN MEDIA AUDIO VISUAL SEBAGAI LAYANAN INFORMASI TERHADAP PEMAHAMAN MASA PUBERTAS SISWA KELAS VII DI SMPN 1 MAJALAYA - Putri Wigati, Ega; Sobari, Teti; Septian, Rezza (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The study aims to find out the influence of audio-visual media in the form of cinematic video to provide information services regarding understanding puberty in girls at SMPN 1 Majalaya which is described into problem formula; 1) The process of developing audio-visual media as an information service; 2) eligibility test of the developed audio visual media; 3) student response to the resulting audio visual media and 4) knowing the effectiveness of the product. The type of research used is a research development or often called Research and Development (R&D). Research and Development research is a research method used to make a product and validate the product so that it is tested by expert validators, namely media experts, material experts and practitioners. The subjects in this study 6 students for limited trials and 10 students for extensive trials all are girls of class VII SMPN 1 Majalaya and have been sampled using purposive sampling that is undergoing puberty. Based on the test results from validators that audio visual media in the form of video information services has an average percentage of 94%, and according to criteria it has been determined that the product is well worth using after the revised results. The results of observation and interviews to teachers and students show a high degree of enthusiasm for the development of video media of this information service to the understanding of puberty. It is related to self-awareness consisting of three aspects: emotional intelligence, personal values and self-evaluation